Narrow-bore core-shell particles and monolithic columns in the analysis of silybin diastereoisomers - Marhol, Petr; Gažák, Radek; Bednář, Petr; Křen, Vladimír (Journal of separation science, 2011)
Two chromatographic narrow-bore columns, a novel 2.6 μm particle-packed Kinetex™ C18 core-shell (50×2.1 mm id) and monolithic Chromolith(®) FastGradient RP-18e (50×2 mm id), were evaluated for the analysis of diastereoisomers of the flavonolignans silybin and 23-O-acetylsilybin under isocratic conditions. The main advantages of the core-shell column are markedly higher efficiency (hmin =2.8 versus 5.6 for silybin A) and better peak symmetry. The Kinetex column exhibits only a slight change in the height equivalent of the theoretical plate with a higher linear velocity of the mobile phase. The monolithic column shows notably higher selectivity in terms of selectivity factor (1.21 versus 1.12) in the analysis of critical-pair of diastereoisomers (silybin A and silybin B) and enables shorter run duration (approx. twofold) together with lower backpressure. The resolution power was found to be comparable, but the Kinetex column required a higher pressure of the mobile phase that, together with the higher chance of clogging, can be a disadvantage in the separation of biological samples. Successful baseline separation of silybin diastereoisomers in real pharmaceutical sample on monolithic column was accomplished.
Keywords: Resins, Synthetic; Chromatography, High Pressure Liquid; Silybin; stereoizomerie; Core-shell; Kinetex; Silymarin; silibinin; syntetické pryskyřice; silymarin; Monolithic column; vysokoúčinná kapalinová chromatografie; Chromolith; Stereoisomerism